Implementation of Tri Hita Karana practices as a strategy to increase tourist attractiveness at Moksa Ubud restaurant - Ni Luh Gede Harinita; Ayu Veronika Somawati (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: This study aims to analyze the application of Tri Hita Karana values in the management of Moksa Ubud Restaurant and their role in attracting tourists. The concept of Tri Hita Karana, rooted in the philosophy of balance between humans and God (Parhyangan), humans and fellow humans (Pawongan), and humans and nature (Palemahan), provides an important basis for developing sustainable culinary tourism practices. Methods: This study uses a qualitative approach, with data collected through observation, in-depth interviews with restaurant managers, and documentation of activities. Data validity is established through source and method triangulation. Findings: The results show that Moksa Ubud Restaurant has successfully implemented Tri Hita Karana in all aspects of its operations. The value of Parhyangan is reflected in the spirituality and gratitude inherent in the work culture of employees; Pawongan is manifested through harmonious relationships between management, employees, and the local community; while Palemahan is applied through environmentally friendly practices such as organic farming, waste management, and the use of local ingredients. The promotional strategy, which highlights sustainability and culinary experiences rooted in local wisdom, has proven effective in attracting tourists, especially ecotourists and millennials. Conclusion: The impact of implementing Tri Hita Karana can be seen in increased tourist visits, economic empowerment of the surrounding community, and the preservation of cultural values and traditional farming practices that directly involve tourists. Novelty/Originality of this article: Thus, the implementation of Tri Hita Karana at Moksa Ubud Restaurant is not only a cultural identity but also a sustainability strategy that strengthens the appeal of culinary tourism in Ubud.